SHPRH together with the Ube2D family of enzymes directly ubiquitinates PCNA at Lys164 in vitro - Xinyang Wang; Yixiong Hu; Yajiao Wen; Miaomiao Shen; Pu Chen; Song Xiang (PLoS ONE, 2026)
Ubiquitin-chain attachment to a highly conserved Lys164 residue in the proliferating cell nuclear antigen (PCNA) signals for template switching events to resume stalled DNA replication. In human cells, the reaction is catalyzed by the ubiquitin ligases SNF2 histone linker PHD RING helicase (SHPRH) or helicase like transcription factor (HLTF), together with the Ubc13-Mms2 ubiquitin conjugating enzyme complex. The reaction requires mono-ubiquitinated PCNA as the substrate. Here, we provide biochemical evidence that SHPRH also directly ubiquitinates unmodified PCNA at Lys164. The reaction requires the Ube2D family of ubiquitin conjugating enzymes and robustly ubiquitinates both free and DNA-bound PCNA. We further found that efficient PCNA ubiquitination requires SHPRH’s HIRAN domain, which mediate interactions with PCNA. Our data suggest another layer of regulation of DNA damage responses through PCNA ubiquitination.